Pengaruh Perubahan Kebijakan Organisasi Terhadap Sikap Resistensi pada Karyawan - Nazmah Nazmah (Jurnal Indonesia Sosial Sains, 2022)
For companies with COVID-19 experiencing a very significant change where the capacity of workers in the room is also limited, the organization modifies the work system from face to face to face to face, the absent system is also modified. This study aims to examine whether there is an effect of changing organizational policies on employee resistance attitudes. In this study using quantitative methods and using a questionnaire as a measuring tool. The scale used in the questionnaire of employee resistance attitudes and changes in company policy uses a Likert scale with 4 choices of statements. Data processing is carried out using a computer system with the SPSS program. Data were collected from 105 scales distributed to permanent employees. Based on the results of the study, it is known that there is a significant effect between employee resistance attitudes to organizational policy changes (F count = 80.278, p <0.05). From this research, it is also known that changes in organizational policies have contributed to the attitude of resistance in employees of PT. SEPC O&M Medan is 43.8% and 56.2% is influenced by other factors. The conclusion of this study the relationship between perceived effectiveness of organizational change and job satisfaction is positive and important. SEPC O & M where employees will react to policy changes made, especially during the current pandemic where there are policy changes that the company cannot predict. These changes make employees demand an attitude of resistance.